STUDI ETNOBOTANI MASYARAKAT SUBETNIS BATAK TOBA DI DESA PEADUNGDUNG, SUMATERA UTARA, INDONESIA - Ria Anggraeni (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
Peadungdung is one of the villages in Indonesia that suffered land forest transforming. Land forest transforming increasing the risk of losing native plant knowledge among community. This risk is difficult to assess because rarely documented. Therefore, ethnobotany approach is needed to document local knowledge about the use of native plants in their environment.Data were collected by interview, direct observation, and inventory. Interview were conducted by 4 key informants and 30 informants. Determination of the informants conducted by purposive sampling technique. A total 163 useful plant species belonging to 66 families were identified and reported. The highest number of plant were used for medicine (92 species), food (71 species), firewood (25 species), Symbol (23 species), local technology (18 species), livestock fodder (18 species), rope (15 species), art (11 species), and revenue (11 species).